Particulate air pollution and metabolic risk factors: Which are more prone to cardiac mortality - Rehman, Erum; Rehman, Shazia (Frontiers in Public Health, 2022)
Objectives: In this study, we sought to explore multiplex, country-level connections between a wide range of cardiac risk factors and associated mortality within the South Asian Association for Regional Cooperation (SAARC) countries. Methods: The grey relational analysis (GRA) methodology is used to evaluate data from 2001-2018 to compute scores and rank countries based on cardiac mortality. Subsequently, using the Conservative (Min-Max) technique, we aimed to discover which South Asian country contributes the most to cardiac mortality. The Hurwicz criterion is further applied to optimize further by highlighting the risk factors with the highest impact on cardiac mortality. Results: The empirical findings reveal that India and Nepal are the leading drivers of CVD mortality among all SAARC nations based on GRA results. Moreover, the outcomes based on the Hurwicz and the Conservative criterion methods indicate that CVD mortality is considerably impacted by household air pollution from combustion of solid fuel, with India as a potential contributor in the SAARC region. Conclusions: The outcomes of this research may enable international organizations and public health policy-makers to make better decisions and investments within the SAARC region to minimize the CVD burden while also strengthening environmentally sustainable healthcare practices.